PENGARUH FAKTOR RESIKO TERHADAP PURCHASE INTENTION - PRIVATE LABEL BRAND TERHADAP MASYARAKAT BATAM - Golan Hasan (Universitas Pelita Harapan Medan Campus, 2017)
Nowadays, the retail industry in Indonesia is booming. Retail outlets in Indonesia has increased by 10-15% each year. To keep up and compete with other retailers, they create their own brands which are known as private label brand. Private label brand is less known and inferior to national brand which causes consumers to question the quality of the product. Thus, consumers perceive risk when a product is less famous. The samples in this study were drawn from consumers who had purchased private label brand groceries in retail shops located in Batam. A total of 360 questionnaires were distributed and 344 questionnaires were qualified to be used in this research. Results show that financial risk, social risk and psychological risk has significant negative effect on purchase intention. On the other hand, functional risk, physical risk, time risk, and value consciousness are insignificant to purchase intention.Keywords: financial risk, functional risk, social risk, physical risk, time risk, psychological risk, value consciousness, purchase intention, private label brand.